Does solar irrigation threaten groundwater sustainability? Evidence from India and Bangladesh - Alam, Mohammad Faiz; Varshney, Deepak; Mitra, Archisman; Pavelic, Paul; Mahapatra, Smaranika; Habib, A.; Krishnan, S.; Sikka, Alok; Ravindranath, Darshini (International Water Management Institute, 2025)
Groundwater irrigation underpins South Asian agriculture but is increasingly unsustainable. Solar irrigation pumps (SIPs) are promoted to cut carbon emissions and subsidy costs, yet concerns persist about over-extraction. This study, under the SDC-supported SoLAR project, assesses two models: fee-for-service SIPs in Bangladesh and grid-connected SIPs in India. Results show no significant rise in groundwater use with solar adoption in these two models. In Bangladesh, operator-managed SIPs kept use in check despite cheaper costs, though some shift toward Boro paddy was noted. In India, grid-connected SIPs with feed-in incentives reduced water use in alluvial aquifers, while hard-rock systems showed little change. The findings highlight that groundwater impacts are context-specific, with well-designed solar models offering low-carbon irrigation without major sustainability risks.